Mr. Louie is screwy! - Gutman, Dan (Gutman, Dan. My weird school ;, 2007)
When the hippie crossing guard, Mr. Louie, puts a love potion in the water fountain before Valentine's Day, everyone at Ella Mentry School falls in love.